2011
DOI: 10.1130/l123.1
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic, dilational-fault and extension-fracture related pit chain formation in Iceland: Analog for pit chains on Mars

Abstract: Pit crater chains are common topographic features on Mars and several other planetary bodies, and a wide range of mechanisms has been proposed for their origin. Two rifting-related seismic events in 1975-1976 and 1978 along the Mid-Atlantic Ridge near the northern coast of Iceland, associated with the Krafl a volcanic eruptions to the south, produced an array of pit chains in unconsolidated sediments overlying Holocene basalt fl ows. Fault scarps and extension fractures in basaltic lava fl ows are traceable la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 42 publications
8
79
0
Order By: Relevance
“…Depending on the amount of dilatancy this process forms either pit craters or large along-strike/elongated collapse grabens. These pit craters were described by Ferrill et al (2004Ferrill et al ( , 2011b on Mars and in Iceland.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Depending on the amount of dilatancy this process forms either pit craters or large along-strike/elongated collapse grabens. These pit craters were described by Ferrill et al (2004Ferrill et al ( , 2011b on Mars and in Iceland.…”
Section: Introductionmentioning
confidence: 95%
“…Van Gent et al (2010) observed dilatant faults in competent carbonates of the United Arab Emirates. Several authors have studied basalts in Hawaii and Iceland which show massively dilatant extensional faults (Gudmundsson and B€ ackstr€ om, 1991;Angelier et al, 1997;Acocella et al, 2000;Holland et al, 2006;Ferrill et al, 2011b). Soden and Shipton (2013) investigated dilational faults on Gran Canaria and found mechanical property variations to be a controlling factor for the development of extension fractures.…”
Section: Introductionmentioning
confidence: 98%
“…Woodcock et al, 2006;Ferrill et al, 2011;Walker et al, 2011). This collapse mechanism grades into other processes: confined implosion at pressure-release zones along faults (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…12f and h). Pit crater chains on Earth and Mars are proposed to form by unconsolidated material draining down into extension fractures and/or dilational normal faults in a more consolidated material at depth (Ferrill et al, 2011;Wyrick et al, 2004). In this scenario the crater chains are pit crater chains and are the surface expression of funnels of down-draining material.…”
Section: Observation and Interpretation Of Structuresmentioning
confidence: 99%